Pelatihan Sertifikasi Halal Self Declare Terhadap Pelaku UMKM di Kelurahan Gunung Anyar Tambak - Muhammad Bagus Yoga Hutama; Ugy Soebiantoro (Politeknik Kampar, 2023)
Indonesia is a country that has the largest Muslim population in the world and has the opportunity to become the center of the global halal industry. However, this has not been implemented because many products from Indonesian MSMEs are still not halal certified, therefore the Indonesian government needs to boost the certification of halal products. The self-declare halal certification training will be held on May 21 at 08.00 – 16.00 at the RW 08 Gunung Kelurahan hall. New Tambak. pond. The training implementation activities were held on May 21, 2023 at 08.00 – 16.00 WIB and carried out at the RW 08 Balai Kelurahan Gunung Anyar Tambak and were attended by 50 MSMEs in Gunung Anyar Tambak sub-district. The Indonesian government continues to strive for Indonesia to become a global halal industry with halal certification training The self-declare held aims to educate and provide an understanding of the importance of halal certification for MSME actors.